Updates in primary aldosteronism - Libianto, Renata (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Primary aldosteronism (PA) is the most common endocrine cause of hypertension, affecting 10% of hypertensive patients in the community and up to 30% of patients with resistant hypertension. Compared to patients with primary hypertension matched for age, sex, and blood pressure, those with undiagnosed and untreated PA have worse cardiovascular outcomes. Effective treatment is available for PA with either mineralocorticoid receptor antagonists or unilateral adrenalectomy, which are effective in treating PA if instituted in a timely manner. However, PA is currently underdiagnosed with a detection rate of <0.1%. In recognition of the importance of PA in the pathophysiology of hypertension, recent hypertension and endocrine guidelines recommended screening for PA in all adults with hypertension. We will discuss updates in PA diagnosis and management with a focus on increasing screening, the role of aldosterone-suppression testing, laboratory method considerations, and emerging treatment options. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S4]